Comparison of Olfactory Genes in Two Ectropis Species: Emphasis on Candidates Involved in the Detection of Type-II Sex Pheromones - Li, Zhao-Qun; Cai, Xiao-Ming; Luo, Zong-Xiu; Bian, Lei; Xin, Zhao-Jun; Chu, Bo; Liu, Yan; Chen, Zong-Mao (Frontiers in Physiology, 2018)
The sibling species Ectropis grisescens and E. obliqua are the major chewing tea pests in China. A difference in sex pheromone components plays a central role in premating isolation in these two species. To investigate the mechanism of premating isolation in these two Ectropis species, we sequenced the transcriptomes of the antennae of female and male E. obliqua individuals and performed phylogenetic analyses, abundance analyses, and tissue expression profile analyses to compare the olfactory genes involved in the detection of sex pheromones. A total of 36 odorant-binding proteins (OBPs) and 52 olfactory receptors (ORs) were identified in E. obliqua. Phylogenetic analyses showed that EoblOBP2, 3, and 25 were grouped in the pheromone-binding protein clade with EgriOBP2, 3, 25, and another lepidopteran PBP. EoblOR25 and 28 were grouped with EgriOR25, 28, and pheromone receptors for the detection of Type-I sex pheromone components. EoblOR24, 31, 37, and 44 were grouped with EgriOR24, 31, 37, and 44. All of these 4 EoblORs and 4 EgriORs showed higher abundance in male antennae than in female ones. Therefore, OBP2, 3, 25 and OR24, 31, 37, 44 of E. grisescens and E. obliqua might be responsible for sex pheromone component detection. However, the sequences of these genes in E. grisescens and E. obliqua were more than 90% identical. This indicates that these orthologous genes might play similar roles in the detection of sex pheromones. In contrast, the observed OBPs and ORs differed in abundance between the antennae of the two Ectropis species. Therefore, we speculate that these two Ectropis species use the different transcript levels of PRs to differentiate sex pheromone components. The results of the present study might contribute in deciphering the mechanism for premating isolation in these species and may be of use in devising strategies for their management.